Determinants Of Liquidity Risk: A Study Of Commercial Banks In Pakistan - Fatima, Syeda Zain; Naseem, Hafiza Iram (Archives of Business Research, 2021)
The aim of this research is to examine the determinants of liquidity risk of commercial banks in Pakistan. For this research, the data of 20 commercial banks of Pakistan is collected annually for eight years ranging from 2012-2020. This study uses the Panel data regression analysis approach. Liquidity ratio as a dependent variable has been selected as measures liquidity risk whereas five independent variables size of bank, liquid assets ratio, capital adequacy ratio, Leverage, Non-performing loans have been selected for different types of bank-specific factors. Fixed effect regression analysis and random effect analysis has been performed, the Hausman test used to see whether the fixed effect model or random model is suitable. The findings of this study are beneficial for policymaker, manager, economic agents to control on risk factors. The results of this study show the size of bank (SOB), liquid assets ratio (LAR), capital adequacy ratio (CAR) has a negative and statistically significant effect on liquidity ratio. However, Leverage (LEV) has a positive and statistically significant effect on liquidity risk meaning that increase in leverage increase the liquidity risk but Non-performing loans (NPLs) has a negative and statistically insignificant relationship with liquidity risk.